2017
DOI: 10.3892/mmr.2017.6240
|View full text |Cite
|
Sign up to set email alerts
|

Slit2 suppresses endothelial cell proliferation and migration by inhibiting the VEGF-Notch signaling pathway

Abstract: Slit homolog 2 (Slit2) is distributed in various tissues and participates in numerous cellular processes; however, the role of Slit2 in the regulation of angiogenesis remains controversial, since it has previously been reported to exert proangiogenic and antiangiogenic activities. The present study aimed to investigate the effects of Slit2 on vascular endothelial cell proliferation and migration in vitro, and to reveal the possible underlying signaling pathway. Aortic endothelial cells were isolated from Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 43 publications
3
21
0
1
Order By: Relevance
“…Our in vitro findings show that the administration of exogenous Slit2 to H-MVECs exerts potent antiangiogenic properties similar to those elicited by Slit2-enriched SSc sera, as testified by the ability to reduce cell viability, wound healing capacity and capillary-like tube formation. This is in agreement with recent reports showing that Slit2 inhibits chemotaxis, migration and invasion of different types of cancer cells42 and suppresses TNF-α-induced cell proliferation and migration of rat aortic endothelial cells 43. Strikingly, we observed that blocking elevated Slit2 in SSc sera resulted in significantly attenuated antiangiogenic effects on administration to H-MVECs.…”
Section: Discussionsupporting
confidence: 93%
“…Our in vitro findings show that the administration of exogenous Slit2 to H-MVECs exerts potent antiangiogenic properties similar to those elicited by Slit2-enriched SSc sera, as testified by the ability to reduce cell viability, wound healing capacity and capillary-like tube formation. This is in agreement with recent reports showing that Slit2 inhibits chemotaxis, migration and invasion of different types of cancer cells42 and suppresses TNF-α-induced cell proliferation and migration of rat aortic endothelial cells 43. Strikingly, we observed that blocking elevated Slit2 in SSc sera resulted in significantly attenuated antiangiogenic effects on administration to H-MVECs.…”
Section: Discussionsupporting
confidence: 93%
“…( B ) Statistical analysis of the apoptotic cell rate in each group. Aortic endothelial cells were isolated from rats as previously described [ 17 ]. ** P <0.01 compared with Sham group.…”
Section: Resultsmentioning
confidence: 99%
“…Aortic endothelial cells were isolated from rats as previously described [ 17 ]. Briefly, rats were anesthetized and killed by rapid cervical dislocation and an incision was quickly made in the abdominal skin, in order to expose the aorta, which was perfused with PBS containing heparin and was then resected.…”
Section: Methodsmentioning
confidence: 99%
“…23 It has been reported that endothelial cells promote the proliferation and differentiation of neural stem cells, possibly by activating the VEGF-Notch pathway, 24 while Slit2 suppress endothelial cell proliferation and migration by inhibiting the VEGF-Notch signaling pathway. 25 The inhibition of cell growth, migration, and promotion of apoptosis induced by delta-tocotrienol are associated with decreased expression of Notch-1 and VEGF. 26 Meanwhile, the inhibition of either VEGF or Notch pathway can regulate cell proliferation and apoptosis through suppressing the expression of cell cycle regulators.…”
Section: Discussionmentioning
confidence: 99%